Peningkatan Wawasan Perencanaan Sdm Dalam Bisnis Bagi Studentpreneur Prodi Manajemen Universitas Muhammadiyah Gresik - Roziana Ainul Hidayati (Jurnal Pengabdian Manajemen, 2022)
Studentpreneur is a student or student who has a business or business, in simple terms it can be said that studentpreneur is a student or student entrepreneur. In conditions like this Covid-19 pandemic, the potential for the emergence of new entrepreneurs is higher, especially in online business. No exception in this case the entrepreneurship of the students. These efforts can be carried out both inside and outside educational institutions with innovative products and generate income from their business activities and based on the knowledge obtained during the study (Pratiwi, 2017). The reasons for students to become entrepreneurs are many factors such as hobbies, pleasure or on the basis of wanting to be independent. Even though they are busy with all learning activities such as doing college assignments, exams or attending lectures, this does not dampen their motivation to become entrepreneurs. Every year there are many high school graduates or undergraduates who become Job seekers so that when they are not absorbed into the workforce, in the end it will only increase unemployment and become a burden for development. Providing assistance and knowledge related to entrepreneurial management, both when entrepreneurship is just being started and when entrepreneurship is running is very important. Providing insight on how to plan finance/capital, plan human resources, plan marketing models that will be used when doing business later is very important. HR planning for businesses is very important to learn considering HR is the most important factor in the success of a business today. If capital difficulties can be managed by partnering with financial institutions, then HR problems are not easy enough to solve because mismanaging HR will have an impact on business in the future. Incorrectly placing and managing people in the business can destroy the business that has been built.